EFFECT OF ANALYTIC PHILOSOPHY ON ENGLISH LANGUAGE EDUCATION - Desi Nosita; Setia Rini (English Language Teaching Journal, 2023)
Language learning cannot be separated from philosophy because philosophy is the mother of science. In its development, language learning was influenced by the philosophy that developed at its time, including analytic philosophy. The influence of Analytic Philosophy is felt in language teaching, especially in semantic and pragmatic research. And Russell's theory of Logical Atomism opens new horizons for scientific research, including linguistics. On the other hand, semantics is an image which is then continued by the theory of meaning used by Wittgenstein as an early study of semantics and pragmatics. Furthermore, the analytical philosophy developed by The Oxford School develops a theory of speech acts that naturally influence language learning, learning is a speech act of language learning. Keywords: Philosophy, analytic, English, pragmatics